The Role of Customer Satisfaction in Mediating the Relationship Between Product Quality and Service Quality on Customer Loyalty at Fore Coffee in Batam - Ellyn Tan; Suhardi (Escalate : Economics and Business Journal, 2026)
This research is motivated by the increasing competition in the modern coffee shop industry, which demands companies to improve product and service quality to create customer satisfaction and loyalty. This study aims to analyze the influence of Product Quality and Service Quality on Customer Satisfaction and Customer Loyalty, and to examine the role of Customer Satisfaction as a mediating variable among Fore Coffee customers in Batam City. The study uses a quantitative approach with a survey method. The study population is all Fore Coffee customers in Batam City, whose number is unknown, while a sample of 119 respondents was determined using the Lemeshow formula with a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-tests, F-tests, and Sobel tests. The results show that Product Quality, Service Quality, and Customer Satisfaction have a positive and significant effect on Customer Loyalty. In addition, Product Quality and Service Quality also have a positive effect on Customer Satisfaction, and Customer Satisfaction is proven to significantly mediate both relationships. This study concludes that increasing Fore Coffee customer loyalty is more effectively achieved through improving product and service quality that can increase customer satisfaction sustainably